Seychelles - Selected Issues : Social Protection, Labor Market and Public Enterprise Reforms - Public Expenditure Review 2 - World Bank (World Bank, 2012)
Until 2008, Seychelles pursued a state-led economic model of self sufficiency which ultimately proved unsustainable. In 2008, precipitated by rising global commodity prices, Seychelles entered a balance of payments and debt crisis, as international reserves were virtually depleted and external debt service payments were missed. The Government of Seychelles responded quickly by floating the rupee and liberalizing the foreign exchange regime, and agreeing a program with the International Monetary Fund under a 2 year stand-by agreement in November 2008. Although the liberalization of the exchange rate in November 2008 led to initial inflation rates in excess of 60 percent, the relative prices shock was quickly absorbed. Annual inflation fell from a high of positive 63.3 percent in December 2008 to negative 1.0 in August 2010. As the price and foreign exchange controls were lifted, the informal market in foreign currency quickly disappeared. This Public Expenditure Review (PER) also provided the Bank with an analytical basis to inform development policy lending in 2010. The specific objectives of the review are to: (i) provide an update on the macroeconomic stabilization efforts and changes to the fiscal policy for medium term debt sustainability and a more efficient and affordable public sector; (ii) analyze key public enterprise reform issues, including a review of the recently introduced legal and institutional changes to improve governance and oversight of the sector; and (iii) review the performance of the social security and labor market and an assessment of the ability of the private sector to absorb employees being retrenched as a result of the civil service reforms.